PENGGUNAAN KALIMAT DALAM LATAR BELAKANG SKRIPSI MAHASISWA PROGRAM STUDI PENDIDIKAN MATEMATIKA TAHUN AKADEMIK 2014 - Novianti, Riska; Sulissusiawan, Ahadi; Wartiningsih, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research is aimed to understanding the use of background sentences in Bachelor degree’s thesis from Mathematic Education Department, Tanjungpura University, at the academic year of 2014. The research variables include four characteristics of effective sentences (Structure Correspondence, Cohesiveness of Idea, Word Austerity & Sentence froms Parallelism and Diction). Data sources taken as samples are bachelor degree’s thesis from Mathematic Education Department , Tanjungpura University, as of academic year 2014. The techniques used for the data collection process was documentary study in wich the key instruments and the researcher are the data collection tools. Based on the results and data analysis. The data in this study are ineffective sentences include errors in structural equivalence, cohesion of ideas, word saving, and parallels form and diction or selection of words on the background of thesis students of the 2014 Academic Year Academic Education Study Program. Data collection techniques in this study are through documentation studies . The data collection tool in this study is the author himself as a key instrument. The validity of the data carried out by the author is the adequacy of the reference by reading and visiting data sources as well as various libraries relevant to the problem under study and triangulating investigators conducted by utilizing research or other observers to check the degree of research data.The results of the research and data analysis concluded that the use of sentences in the background of the thesis students of the 2014 Academic Education Study Program 2014 contained 162 sentence writing errors, namely first, structural equivalence errors had 44 errors. Second, there are 21 mistakes for the two ideas. Third, there are 31 word-saving errors. Fourth, there are 1 error in form and kelimat there are 60 errors in diction.Keywords:Background of Thesis, SentenceAbstractThis research is aimed to understanding the use of background sentences in Bachelor degree’s thesis from Mathematic Education Department, Tanjungpura University, at the academic year of 2014. The research variables include four characteristics of effective sentences (Structure Correspondence, Cohesiveness of Idea, Word Austerity & Sentence froms Parallelism and Diction). Data sources taken as samples are bachelor degree’s thesis from Mathematic Education Department , Tanjungpura University, as of academic year 2014. The techniques used for the data collection process was documentary study in wich the key instruments and the researcher are the data collection tools. Based on the results and data analysis. The data in this study are ineffective sentences include errors in structural equivalence, cohesion of ideas, word saving, and parallels form and diction or selection of words on the background of thesis students of the 2014 Academic Year Academic Education Study Program. Data collection techniques in this study are through documentation studies . The data collection tool in this study is the author himself as a key instrument. The validity of the data carried out by the author is the adequacy of the reference by reading and visiting data sources as well as various libraries relevant to the problem under study and triangulating investigators conducted by utilizing research or other observers to check the degree of research data.The results of the research and data analysis concluded that the use of sentences in the background of the thesis students of the 2014 Academic Education Study Program 2014 contained 162 sentence writing errors, namely first, structural equivalence errors had 44 errors. Second, there are 21 mistakes for the two ideas. Third, there are 31 word-saving errors. Fourth, there are 1 error in form and kelimat there are 60 errors in diction. Keywords:Background of Thesis, Sentence